2020
DOI: 10.1126/science.abc6284
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccine protection against SARS-CoV-2 in rhesus macaques

Abstract: The global COVID-19 pandemic caused by the SARS-CoV-2 virus has made the development of a vaccine a top biomedical priority. In this study, we developed a series of DNA vaccine candidates expressing different forms of the SARS-CoV-2 Spike (S) protein and evaluated them in 35 rhesus macaques. Vaccinated animals developed humoral and cellular immune responses, including neutralizing antibody titers comparable to those found in convalescent humans and macaques infected with SARS-CoV-2. Following vaccination, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

84
1,238
5
12

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 1,066 publications
(1,367 citation statements)
references
References 29 publications
84
1,238
5
12
Order By: Relevance
“…During the SARS and MERS outbreaks, NHP models were developed with a moderate degree of success 3 . Early reports also indicate the utility of NHPs for SARS-CoV-2 infection, and for evaluating vaccine candidates 4, 5, 6, 7 . We hypothesized that the heterogeneity of human responses to SARS-CoV-2 infection can be recapitulated using multiple NHP species.…”
Section: Mainmentioning
confidence: 99%
“…During the SARS and MERS outbreaks, NHP models were developed with a moderate degree of success 3 . Early reports also indicate the utility of NHPs for SARS-CoV-2 infection, and for evaluating vaccine candidates 4, 5, 6, 7 . We hypothesized that the heterogeneity of human responses to SARS-CoV-2 infection can be recapitulated using multiple NHP species.…”
Section: Mainmentioning
confidence: 99%
“…SARS-CoV-2 fuses with and enters host cells following engagement of its surface spike (S) protein with human angiotensin-converting enzyme 2 (hACE2) 18,19 , which is expressed on multiple tissues, notably including the lung alveolar epithelium and vascular endothelium, and also in the liver, colon, esophagus, small intestine, duodenum, kidney, brain, and tongue [20][21][22] . A number of investigators are currently setting up animal models susceptible to SARS-CoV-2 infection such as mice, ferrets, hamsters, rats, and monkeys [23][24][25][26][27] , but earlier studies have indicated that, due to species differences, these models cannot recapitulate key aspects of the human anti-viral, immune, and pathological responses to coronaviruses 28 .…”
Section: Introductionmentioning
confidence: 99%
“…This has important implications for COVID-19 vaccine development as virus-specific T cells are thought to play an important role in SARS-CoV-2 infection [18][19][20][21][22] . While no correlate of protection has been defined for COVID-19, recent publications suggest that neutralising antibody titres may be correlated with protection in animal challenge models 23,24 . A single dose of ChAdOx1 nCoV-19 induces antibody responses, but we demonstrate here that antibody responses are significantly enhanced after homologous boost in one mouse strain and to a greater extent in pigs.…”
Section: Discussionmentioning
confidence: 99%